The new IAB-SOEP migration sample: An introduction into the methodology and the contents - Herbert Brücker; Martin Kroh; Simone Bartsch; Jan Goebel; Simon Kühne; Elisabeth Liebau; Parvati Trübswetter; Ingrid Tucci; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
[Introduction ...] The remainder of this paper describes the development and special features of the IAB-SOEP Migration Sample and gives an overview of the questionnaire. The IAB-SOEP Migration Sample builds both on previous experience surveying migrants in the SOEP as well as on past experience with migration research based on register data such as the Integrated Employment Biographies (IEB) data set. Section 2 discusses how the changing socio-economic structure of migration to Germany and the limitations of register data and previous surveys have created a growing need for a survey of this kind - in particular, one that links survey and register data. Section 3 describes the procedure used to draw the sample and the weighting procedure. To the best of our knowledge, the IAB-SOEP Migration Sample constitutes the first use of IEB data as a sampling frame. This has a number of implications for the survey. Section 4 presents the content of the questionnaire used in the IAB-SOEP Migration Sample and the key similarities and differences compared to the standard SOEP questionnaire. Section 5 describes the linkage of the survey data and the IEB register data, as well as the data products that are produced. Since we cannot present all issues in detail here, we have included references to in-depth survey papers in the relevant sections.
Keywords: 330